MENINGKATKAN KEMAMPUAN MENGENAL BENTUK-BENTUK GEOMETRI MELALUI MEDIA PUZZLE (BONGKAR PASANG) PADA ANAK USIA 4 – 5 TAHUN DI TK PERTIWI KABUPATEN GOWA - Abd Hakim Naba (Fakultas Keguruan dan Ilmu Penidikan UIM, 2018)
The study aims to determine the ability to recognize geometric forms through media puzzles (unloading pairs) in early childhood 4-5 years in TK Pertiwi, Gowa Regency. This research is a classroom action research with 30 research subjects. Data collection techniques use puzzles (unloading). The study was conducted through two cycles, with each cycle consisting of four stages, namely planning, implementation, observation and reflection. The results of data analysis obtained in the first cycle the average percentage of completeness in learning the introduction of geometric forms have not reached the indicator that is equal to 54.81%, while the average percentage of completeness in learning the introduction of geometric shapes in students in the second cycle activities has developed which is very good at 78.89%. This study shows a significant increase in the introduction of geometry. The results of this research show that puzzle games can improve the introduction of geometry in 4-5 year old children in TK Pertiwi, Gowa Regency.Keywords: Geometry, Puzzle Games (Unloading)